"Stop Thinking Like a Social Scientist and Start Thinking like an Artist": The Research-Based Aesthetic Product. Issue 4 (November 2019) - Teman, Eric D.; Saldaña, Johnny
The coauthors first discuss their individual perspectives on arts-based qualitative research, their development as artists, and their later collaboration on an ethnodramatic screenplay as an artistic project. The coauthors then describe their next collaboration: the adaptation of a college-aged, gay, ex-Mormon's life story from interview transcripts into three artistic literary renderings: the prosaic, poetic, and dramatic. The prosaic narrative vignette presents an awkward meeting between the young gay man and his ROTC faculty advisor. The poetic rendering focuses on his tense, estranged family relationships during his brother's wedding. And the monologic, ethnodramatic version portrays his turning point in gay identity and self-acceptance. The article concludes with the coauthors' reflections on their literary representations' artistic and aesthetic efficacy.